Constitutional Disobedience Be the Reason for the Impeachment of the President and/or Vice President During the Term of Office - H. Muhamad Rezky Pahlawan MP; O. Djunaedi; Atma Suganda (PT FORMOSA CENDEKIA GLOBAL, 2025)
The dismissal of the President and/or Vice President is a legislative authority involving the DPR, MPR, and the Constitutional Court (MK) to address constitutional or legal violations. This study examines constitutional defiance by the President/Vice President and the reconstruction of the ideal mechanism for their dismissal. With a normative legal approach, this study concludes that reporting violations can be done by citizens or organizations because sovereignty lies in the hands of the people. Reconstruction of the ideal mechanism is suggested through national legal reform based on Pancasila values, including the preparation of special procedural law for the dismissal of the President/Vice President that is adjusted to the amendments to the 1945 Constitution.